1967
DOI: 10.1017/s0021859600017809
|View full text |Cite
|
Sign up to set email alerts
|

The growth of lambs grazing on perennial ryegrass, tall fescue and cocksfoot, with and without white clover, as related to the botanical and chemical composition of the pasture and pattern of fermentation in the rumen

Abstract: 1. An experiment was conducted in which lambs grazed on pastures of cocksfoot, ryegrass and tall fescue grown with and without white clover, as well as on pastures of pure white clover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

1967
1967
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 22 publications
3
35
1
Order By: Relevance
“…The marked advantage of legumes over grasses in this respect is suggested to be a combination of a higher voluntary dry matter intake of the legumes (McLean et al 1965;Grimes et al 1967). a high proportion of propionic to acetic acid in the rumen liquor (Johns.…”
Section: (B) Carcass Weightmentioning
confidence: 99%
See 2 more Smart Citations
“…The marked advantage of legumes over grasses in this respect is suggested to be a combination of a higher voluntary dry matter intake of the legumes (McLean et al 1965;Grimes et al 1967). a high proportion of propionic to acetic acid in the rumen liquor (Johns.…”
Section: (B) Carcass Weightmentioning
confidence: 99%
“…Ulyatt. and Glenday 1963;McLean et al 1965;Grimes et al 1967); and more efficient utilisation of energy by animals ingesting legumes (Joyce and Newth 1967).…”
Section: (B) Carcass Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible, that this superiority was due to the slightly higher WSC content of tetraploid varieties (Smith et al 2001;Gilliland et al 2002). Grimes et al (1967) also found strong positive correlation between WSC content and intake and liveweight gain of lambs. On the basis of published data, it is suggested that increased WSC, particularly in the vegetative leaf and in the summer/autumn period when CP is frequently in excess, would improve herbage quality.…”
Section: Conclusion and Grass Breeding Strategymentioning
confidence: 87%
“…High WSC content is an important breeding goal for milk production and liveweight gain. Over a range of species, Grimes et al (1967) found strong positive correlation between WSC content and intake and liveweight gain of lambs. In the last decade, few improved ryegrass varieties had been bred for increase WSC concentration, in UK (Wilkins and Lovatt 2007;Wilkins et al 2010), and New Zealand (Rasmussen et al, 2009).…”
Section: Introductionmentioning
confidence: 90%